THE PERCEPTION OF “THE OTHER” BY THE HIGH SCHOOL STUDENTS AND THE TOLERANCE - Makarevičs, Valērijs; Iliško, Dzintra; Tolmačova, Jūlija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The issue of tolerance has been actively discussed in psychology. Psychological science has to solve a number of important methodological problems related to the etiology of this term. Adolescence is the time then one’s identity is being formed. This can be assumed by the authors that the pupils with a positive identity are more tolerant towards "others." The hypothesis of the study: Positive attitude influence the perception of “tolerant” schoolchildren by the “other” to a greater extent. The perception of the “other” by “intolerant” schoolchildren is more subject to negative stereotyping. For the purpose of the study, a methodology for measuring tolerance was developed. It included scales of measuring interpersonal and intergroup tolerance. In addition, expert teachers avaluation of pupils were used. Based on their assessments, two groups of pupils were formed. One of them experts rated as “good” pupils. They received higher marks on the tolerance scale. The second group of pupils, according to the experts’ evaluation, had serious problems with discipline at school. They received low marks on the tolerance scale. This group of pupils was called "hooligans." The results of the study indicate that tolerant students have no significant differences in the perception of “themselves” and “strangers.” The perception of “hooligans” shows a polarization effect: “they” are perceived only positively but "strangers".